A escritura do avesso : o dizer do inominável em Menino do Mato - Sales, Joémerson de Oliveira (2016)
This research presents the writing notion to understand the real and fictional binomial within the poem Menino do mato. Through these spaces we can recognize the lyric voices who want to unsee the world. This research brings the unsee act as a device to unravel the circularity present in this Manoel de Barros’s masterpiece. According to Alfredo Bosi, the poet looks back on his childhood searching for new meanings to his experiences and looking for freedom. He desires to run away from the emptiness to dive into the depth of the senses. The inaugural look of the I-lyrical projects pictures through the prefix “un” which creates new expressions, such as “unsee” and “unopened”. These aspects allude to the concept of cheating from Roland Barthes’s studies. According to Barthes, cheating is a strategy used to express through words something from an unamenable order. This research conceives this phenomenon as a way to play with fiction and reality. Moreover, it is in the verses of literature we look for some pieces of reality. It may be perceived through the incessant desire of the ILyrical to use the bird words. This desire lead us to Jacques Lacan’s studies, which shows that the desire is connected to metonymy. In this sense, it is possible to notice that the I-Lyrical makes a circular journey and, along his way, he has to deal with his own will of embellishing the poetry – this is the key point of the reading. Thus, this research is based on the semiotic studies of Roland Barthes and some assumptions from Jacques Lacan and Jacques Derrida, among other authors. Our analysis highlights three main elements of the poem: the unsee; the wanted and the bird words. These elements dialogue with our theoretical references. We analyze these aspects through an interpretative panorama that arises from the idea of a game with fiction and reality stablished from Barthes’s theory about cheating. Therefore, the aim of this research is to investigate the scopic drive in the poem Menino do mato, building an appraisal of this poetry without, however, exhaust the meanings of this masterpiece.